MapZ deficiency leads to defects in the envelope structure and changes stress tolerance of Streptococcus mutans. (16th September 2021) - Li, Yongliang; Qiao, Dan; Zhang, Yifei; Hao, Weifeng; Xi, Yue; Deng, Xuliang; Ge, Xuejun; Xu, Mingming
Abstract: Cell division is a central process in bacteria and a prerequisite for pathogenicity. Several proteins are involved in this process to ensure the accurate localization and proper function of the division machinery. In Streptococcus mutans, MapZ marks the division sites and position of the Z‐ring to regulate cell division; however, whether MapZ deficiency can impair the cariogenic virulence of S. mutans remains unclear. Here, using a phenotypic assay and RNA‐seq, we investigated the role of MapZ in cell envelope maintenance, biofilm formation, and stress tolerance in S. mutans . The results show that MapZ is important for normal cell shape and envelope structure, and its deletion causes abnormal septum structure and a thin cell wall. Subsequently, we found that the absence of MapZ leads to a greater level of cell death within 12 h biofilms, but it does not seem to affect biofilm architecture and accumulation. mapZ deletion also results in a decreased acid and osmotic stress tolerance. Furthermore, RNA‐seq data reveal that MapZ deficiency causes changes in the expression levels of genes involved in transport systems, sugar metabolism, nature competence, and bacteriocin synthesis. Interestingly, we found that mapZ mutation renders S. mutans more sensitive to chlorhexidine. Taken together, our study suggests that MapZ plays a role in maintaining cell envelope structure and stress tolerance in S. mutans, showing a potential application as a drug target for caries prevention.